PENGGUNAAN MODEL PROBLEM BASIC LEARNING PADA MATERI PIKTOGRAM UNTUK MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN SISWA KELAS IV SDN 02 DEMANGAN KOTA MADIUN - Asna Alfinnisa; Pujiati; Agustina Ika Widya Gunita (STKIP Subang, 2024)
This research is motivated by the need for innovative teaching methods in the education field to increase student enthusiasm during the learning process. The type of research used is Classroom Action Research (CAR). The purpose of this research is to determine whether there is an improvement in learning outcomes and student activity using the Problem-Based Learning (PBL) method in the teaching process of pictogram material for fourth-grade students at SDN 02 Demangan, Madiun City. Data collection techniques involve tests and observations. The subjects of this research are the fourth-grade students of SDN 02 Demangan, totaling 24 students. The results of this study indicate that there is an improvement in the learning outcomes of fourth-grade students at SDN 02 Demangan regarding pictogram material using the Problem-Based Learning model. In the first cycle, the average learning outcome of students was 67.08, which increased to an average of 86.25 in the second cycle. The results of the study on student activity in the pictogram material with the Problem-Based Learning model also showed a 17% increase, from 54% in the first cycle to 71% in the second cycle. The results from the first cycle were still in the low category, whereas the second cycle results were in the moderate category. This indicates that the use of the Problem-Based Learning model can enhance student activity in learning. Changes in students can be observed in their enthusiasm for participating in lessons, the interaction between teacher and students, students with students, and students appearing more active in lessons designed by the teacher.